Country portfolios with heterogeneous pledgeability - Tommaso Trani (Graduate Institute of International and Development Studies, 2012)
In a two-country portfolio model with leverage constraints, I focus on private assets in order to understand how their behaviour can justify an expected excess return as well as the flight-to-safety observed in the data. The specific goal is to study how much these phenomena are explained by the fact that investors cannot always borrow the same amount of resources pledging domestic assets as pledging foreign collateral. Modeling the leverage constraints accordingly, I propose a methodology to deal with this heterogeneous pledgeability and solve for country portfolios. The central feature of this approach is that any idiosyncratic shocks generate an expected excess returns which compensate the current effects of the shock on the relative riskiness of local versus foreign collateral. The resulting portfolio solution shows that, in equilibrium, investors care for this risk and renounce to a part of the expected excess return - favouring current borrowing. The main consequences are: the home equity bias is smaller than in a model where assets are homogeneously pledgeable; the ex post dynamics of the relative premium paid on collateralized assets contribute to the cross-border transmission of shocks. Given these dynamics, idiosyncratic shocks to the pledgeability of local assets affect the value of external claims and liabilities of the country hit by the shock in such a way that its net foreign assets match those observed in the data during times of flight-to-safety.
Keywords: E44; F32; F41; G11; G15; 330; portfolio choice; riskiness of pledged collateral; return differentials; macroeconomic interdependence; Portfolio-Management; Kapitaleinkommen; Zwei-Länder-Modell; Offene Volkswirtschaft; Theorie